Uji Kelayakan dan Respon Siswa Pada Media Pembelajaran Jam Pintar Materi Waktu di Kelas 2 SD NU Tanwirul Qulub - Putri Jenar Mahesa Ayu; Aulia Rohmah; Sania Rizka Faiza; Abelia Helga Natasya; Ika Ari Pratiwi (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to develop and test the feasibility of Smart Clock learning media as an aid in learning mathematics on time material in grade 2 of SD NU Tanwirul Qulub. The media is designed as a three-dimensional analog clock that can be adjusted by students to facilitate understanding of the concept of time units in a concrete and fun way. This study applies the ADDIE development model, which includes the stages of analysis, design, and development. The validation process was carried out by material experts and media experts, each carried out twice. The validation results showed an increase in scores from 60% to 90% in material validation, and from 92% to 96% in media validation, indicating that the media is included in the